2016
DOI: 10.1016/j.alit.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented gelsolins are increased in rheumatoid arthritis-associated interstitial lung disease with usual interstitial pneumonia pattern

Abstract: Fragmented gelsolins may be associated with the pathogenesis of fibrosis in RA-ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In addition, Landi’s team found that 14-3-3ϵ was increased in the BALF proteome of SSc-ILD patients compared with nonsmokers ( 18 , 20 ). In inflammatory and autoimmune diseases, 14-3-3-ϵ, as a component of the TNFR2 complex, restricts the activation of NF-κB through PI3K/Akt/mTOR signaling and stimulates the activation of C/EBP-β, thus guiding the plasticity of macrophages ( 43 ).…”
Section: Proteomics Studies In Different Ctd-ild Subtypesmentioning
confidence: 99%
“…In addition, Landi’s team found that 14-3-3ϵ was increased in the BALF proteome of SSc-ILD patients compared with nonsmokers ( 18 , 20 ). In inflammatory and autoimmune diseases, 14-3-3-ϵ, as a component of the TNFR2 complex, restricts the activation of NF-κB through PI3K/Akt/mTOR signaling and stimulates the activation of C/EBP-β, thus guiding the plasticity of macrophages ( 43 ).…”
Section: Proteomics Studies In Different Ctd-ild Subtypesmentioning
confidence: 99%
“…Accordingly, BAL with cellular analysis is now formally recommended to assist in the diagnosis of CHP ( 181 ) and has received a conditional recommendation for excluding other potential ILD causes when diagnosing IPF ( 182 ). BAL protein biomarkers may help differentiate ILD subtypes, including organizing pneumonia from UIP in patients with RA-ILD ( 183 ), IPF from other forms of ILD ( 93 , 184 186 ), as well as CHP from IPF ( 100 ). Exhaled breath analysis of volatile organic compounds is an evolving, but promising modality for discriminating ILD subtypes that may 1 day provide a non-invasive alternative to BAL ( 187 ).…”
Section: Airway Biomarkersmentioning
confidence: 99%
“…Nevertheless, the less common organizing pneumonia (OP) and lymphocytic interstitial pneumonia are not as rare as hypothesized. The proteomic profiles of UIP and OP were compared by Suhara et al [38] by analyzing BALf of patients with 2-DE and nano-LC-ESI-MS/MS. The levels of the fragmented proteins gelsolin and Ig kappa chain C region were found to be significantly higher in UIP patients compared to those with an OP pattern.…”
Section: Rheumatoid Arthritis-associated Lung Diseasementioning
confidence: 99%
“…Among others, the authors observed that retinol-binding protein 4 (RBP4) and fetuin-A were significantly lowered in patients with active TB compared to controls, thus suggesting that they could be considered potential biomarkers for monitoring the course of the disease during clinical treatment. [32,[35][36] Lung fibrosis associated to SSc BALf [32,37] RA-ILD BALf [38] PLCH BALf [32,39] CF Serum [41] COPD BALf [29,30,44,46,47] IPAH Serum [48][49][50] TB Serum [61] Electrophoresis -Life Sciences Practical Applications…”
Section: Tuberculosismentioning
confidence: 99%